Optimal design of heating and cooling pipeline networks for residential distributed energy resource systems. (15th November 2021) - Clarke, Fiona; Dorneanu, Bogdan; Mechleri, Evgenia; Arellano-Garcia, Harvey
Abstract: This paper presents a mixed integer linear programming model for the optimal design of a distributed energy resource (DER) system that meets electricity, heating, cooling and domestic hot water demands of a neighbourhood. The objective is the optimal selection of the system components among different technologies, as well as the optimal design of the heat pipeline network to allow heat exchange between different nodes in the neighbourhood. More specifically, this work focuses on the design, interaction and operation of the pipeline network, assuming the operation and maintenance costs. Furthermore, thermal and cold storage, transfer of thermal energy, and pipelines for transfer of cold and hot water to meet domestic hot water demands are additions to previously published models. The application of the final model is investigated for a case-study of a neighbourhood of five houses located in the UK. The scalability of the model is tested by also applying the model to a neighbourhood of ten and twenty houses, respectively. Enabling exchange of thermal power between the neighbours, including for storage purposes, and using separate hot and cold pipeline networks reduces the cost and the environmental impact of the resulting DER. Highlights: The domestic hot water demand for the small neighbourhood can be met by the system. Thermal energy stored can be distributed to other nodes via the pipeline network. Houses can send their self-generated thermal energy to a storage tank located in another house via the pipeline network. The operational and maintenance costs of the pipeline network are accounted for in the overall annual costs of the system. The optional use of a biomass boiler (BB) to meet space heating and domestic hot water demands.